Development of robot motion direction based on microcontroller with compass sensor - Seke, Fransiskus Royke; Tamba, Ibadja Parsaoran (Institute of Advanced Engineering and Science, 2024)
This research brings innovation to the motion and navigation system of the ‘DK-ONE’ robot. In the 2021 Indonesian ‘Search and Rescue’ robot contest, the ‘DK-ONE’ robot faced difficulties moving towards the target room. The issue was attributed to an unbalanced frame construction and friction between the robot’s legs and the arena floor, leading to leg slippage. This resulted in a mismatch between the programmed number of steps for the robot and the desired path to the target space, causing errors in the robot’s system. To address these problems, researchers conducted a study aimed at enabling the ‘DK-ONE’ robot to accurately determine its direction of motion. This research followed the waterfall method, involving stages such as system analysis, design, coding, testing, and supporting phases. The study was carried out in the integrated laboratory of the Department of Electrical Engineering Education. The development of the robot’s motion direction using a compass sensor significantly improved stability while walking on straight, flat, and uneven paths. The robot no longer experienced errors in its motion direction and remained on the intended path. As a result, the increased efficiency in robot motion also positively impacted the structural efficiency and energy consumption of the robot.